Бортова діагностична система транспортного засобу - Падалка, О. С. (ХНУРЕ, 2021)
A modern vehicle consists of four main units: engine, body, base and chassis. These units ensure the main function of vehicles - safe operation. But in order for the operation to be safe and comfortable, and the main units to work flawlessly, the vehicles are equipped with a fairly large number of various devices, which are commonly called on-board equipment.
Keywords: діагностична система транспортного засобу